A randomized controlled trial of statin therapy effect on androgen status and erectile function in men with high and very high cardiovascular risk (TRISTAN): rationale and study protocol - K. P. Raevskii; O. Yu. Nesterova; A. A. Strigunov; M. E. Chaliy; A. V. Kadrev; A. G. Plisyuk; A. A. Kamalov; Ya. A. Orlova (Рациональная фармакотерапия в кардиологии)
Aim. To study the effect of different intensities of statin therapy on androgen status and erectile function in men aged 40-65 years with high and very high cardiovascular risk. Additionally, to assess the association between sex hormone levels, erectile function parameters, and traditional cardiovascular risk factors, arterial stiffness, and endothelial function in this patient category.Material and methods. It is planned to conduct a prospective randomized controlled trial, including 150 male patients aged 40-65 years, undergoing routine preventive examinations in the clinic of Moscow State University, having a high and very high risk of CVD and meeting the inclusion criteria. Group 1 (n=75) will receive pitavastatin at a starting dose of 1 mg/day. Group 2 (n=75) will receive rosuvastatin 20 mg/day. After 3 months, the biochemical parameters will be monitored, and dose titration of pitavastatin to 2-4 mg/day and/or rosuvastatin to 40 mg/day will be performed if necessary. Patient recruitment to the study will occur over 9 months at a single research center. Patients will be monitored with an objective assessment of erectile function parameters, blood analysis (including androgen status), central arteries stiffness, and endothelial function for 6 months from the moment of activation. Follow-up visits are scheduled at 1, 3 and 6 months.Results. The expected result of testing the research hypothesis is that statin therapy will not have a negative effect on androgen status and erectile function in men. Intensive statin therapy will have a greater positive effect on endothelial function, which may lead to an improvement in men’s erectile function.Conclusion. The study was planned under the assumption that statin therapy would not have a negative effect on androgen status and erectile function in men aged 40-65 years. It is also suggested that the positive effect of statins on endothelial function and vascular stiffness may lead to an improvement in erectile function among men with high and very high cardiovascular risk. If the hypothesis is confirmed, the results obtained will help improve statin treatment adherence in male patients and, as a result, increase the effectiveness of prevention of cardiovascular events.